The impact of financial literacy, campus environment, and lifestyle the consumptive financial management students - Istiqomah, Anisa; Nugraheni, Krisnawati Setyaningrum (Jurnal Mantik, 2024)
This research aims to determine the influence of financial literacy, campus environment, and lifestyle on the consumer financial management of online shopping among STIEPARI Semarang students. This is a quantitative research study. The population and sample in this study are STIEPARI Semarang students, with a total of 95 respondents. This study uses multiple linear regression analysis to analyze and test the hypotheses. The results of this study show that the first variable, The Effect of Financial Literacy, has a positive and significant impact on Consumer Financial Management of Online Shopping among STIEPARI Semarang Students; the second variable, Campus Environment, has a positive and significant effect on Consumer Financial Management of Online Shopping among STIEPARI Semarang Students; the third variable, Lifestyle, has a positive and significant influence on Consumer Financial Management of Online Shopping among STIEPARI Semarang Students; and the fourth variable, The Influence of Financial Literacy, Campus Environment, and Lifestyle, together have a positive and significant impact on Consumer Financial Management of Online Shopping among STIEPARI Semarang Students